(untitled) (Journal of Fiber Bioengineering and Informatics, 2024)
Chinese embroidery is an important traditional craft that holds cultural significance and reflects the essence of Chinese culture. With the rise of the cultural creative industry, there is a growing demand for innovative approaches to incorporating Chinese embroidery into a wide range of products. However, a research gap exists regarding methods to address this integration’s unique challenges and opportunities adequately. Therefore, this study explores the integration of Chinese embroidery into cultural and creative product design through the synergistic utilisation of the Analytical Hierarchy Process (AHP), Quality Function Deployment (QFD) and the Theory of Inventive Problem Solving (TRIZ). This approach presents a holistic and streamlined design methodology. AHP and QFD are employed to address customer requirements, whereas TRIZ is employed to overcome technical obstacles and foster innovative solutions. This study aims to bridge the research gap by combining qualitative and quantitative methods to explore solutions for integrating Chinese embroidery into cultural and creative product design, tapping into its diverse artistic and cultural potentials. The research objective is to inspire the development of more innovative and culturally significant products, integrating the elements and aesthetics of Chinese embroidery into cultural and creative product design. The significance of this study lies in its incorporation of systematic methods and methodological innovation. Designers can create products that preserve and promote the rich heritage of Chinese embroidery within the realm of cultural and creative product design, ensuring its sustainability and evolution within the cultural creative industry.